2019
DOI: 10.3390/su11092661
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Municipal Solid Waste into Construction Materials

Abstract: Rapid urbanisation and the associated infrastructure development are creating a deficit of conventional construction materials and straining the natural resources. On the other hand, municipal solid waste (MSW) disposal poses a serious environmental problem. Landfilling of MSW is both costly and polluting. Incineration of MSW to generate energy is a commonly adopted approach. However, there are concerns associated with micro pollutants emitted from the combustion process. The carbon footprint of the process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…It was concluded that, using Malaysian cement and aggregates instead of the corresponding Singapore materials, the high-strength concrete potential and embodied energy reduced to 11% and 31%, respectively. e effects of by-products' usage and waste materials as supplementary cementitious systems have been also extensively investigated [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As a result, fly ashes [21,27], metakaolin [30], geopolymers [31,32], slags (such as steel slags) [24,25], and sugar cane bagasse ash [33][34][35][36] were added to green concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that, using Malaysian cement and aggregates instead of the corresponding Singapore materials, the high-strength concrete potential and embodied energy reduced to 11% and 31%, respectively. e effects of by-products' usage and waste materials as supplementary cementitious systems have been also extensively investigated [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As a result, fly ashes [21,27], metakaolin [30], geopolymers [31,32], slags (such as steel slags) [24,25], and sugar cane bagasse ash [33][34][35][36] were added to green concrete.…”
Section: Introductionmentioning
confidence: 99%
“…These composite plastics have to be landfilled because they are difficult to separate by conventional mechanical and/or chemical recovery processes (Al-Salem et al, 2009 ; Astrup et al, 2009 ; Singh et al, 2017 ). Recent approaches for valorizing mixed PWs include mixing them with materials such as wood, cement, and ash to turn them into construction materials (Sardot et al, 2012 ; Sofi et al, 2019 ), printable paper-like composites (Fan et al, 2020 ), fiber composites (Keskisaari and Kärki, 2017 ), new polymers (Rahimi and Garciá, 2017 ), and polar waxes (Marek et al, 2015 ). Nanomaterials have also been prepared from single-polymer PW.…”
Section: Waste As Starting Materials For the Production Of Nanoparticmentioning
confidence: 99%
“…However, it is the least environmentally friendly means of MSW disposal; the use of landfills reduces the efficiency of waste disposal and even causes serious problems, such as groundwater contamination and air pollution with the release of harmful gases from landfill and soil contamination [7]. Incineration can generate electricity, but micro-pollutants emitted from the combustion process are also a concern [8]. In recent years, due to the low efficiency of waste disposal and the above problems, landfills have rarely been used.…”
Section: Introductionmentioning
confidence: 99%